A comparative study of the behaviour/stress distribution (tensional forces) around short and standard length implants on the posterior area to the maxilla. Finite element analysis - Loyola González, Pablo Octavio (2014)
Fil: Loyola González, Pablo Octavio. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra Prostodoncia IV B; Argentina